الدفتر العقاري كسند لإثبات الملكية العقارية الممسوحة - منجي بوشوك; أسامة مبروكي (My University, 2019)
Summary: Although the legislator has identified a range of legal means and methods that demonstrate real estate ownership However, the real estate book is the only means of proof of real property ownership in the surveyed areas, It is an administrative bond issued by the real estate governorate After the completion of the physical and legal procedures relating to the general land survey process and the establishment of the Land Registry until the receipt of the land book, Disputes arise over the real estate book in respect of cancellation and compensation proceedings Therefore, jurisdiction is vested in the judiciary, so the Algerian legislator has severed the legal value of the real estate book. as the only bond in the surveyed areas and hence the dispensing of other contracts. .......................... الملخص : بالرغم من أن المشرع قام بتحديد مجموعة من الوسائل القانونية و الطرق التي تثبت الملكية العقارية ، إلا أن الدفتر العقاري يعتبر الوسيلة الوحيدة للإثبات الملكية العقارية في المناطق الممسوحة ، وهو عبارة عن سند إداري يصدر من طرف المحافظة العقارية ، هذا بعد إتمام الإجراءات المادية والإجراءات القانونية المتعلقة عملية مسح الأراضي العام وتأسيس السجل العقاري الى غاية إستلام الدفتر العقاري ، وتثار منازعات بشأن الدفتر العقاري في ما يخص دعوى الإلغاء و دعوى التعويض ، وبالتالي هنا فإن الإختصاص يؤول للقضاء ، ولذلك المشرع الجزائري قد قطع بشأن القيمة القانونية للدفتر العقار ، بإعتباره السند الوحيد في المناطق الممسوحة و بالتالي الإستغناء عن العقود الأخرى . ....................... Résumé : Bien que le législateur ait identifié un éventail de moyens et de méthodes juridiques qui démontrent la propriété immobilière, le livre immobilier est le seul moyen de prouver la propriété immobilière dans les zones étudiées, Il s’agit d’un cautionnement administratif émis par le gouvernorat immobilier Après l’achèvement des procédures physiques et juridiques relatives au processus général d’arpentage et à l’établissement du registre foncier jusqu’à la réception du cadastre, Par conséquent, la compétence est dévolue au pouvoir judiciaire, de sorte que le législateur algérien a supprimé la valeur légale du livre immobilier. en tant que seul cautionnement dans les zones étudiées et, par conséquent, l’exécution d’autres contrats.